*It happens the same: actividades para la enseñanza de los verbos inacusativos a aprendientes del inglés como L2 - Saade, Andrea (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2023)
In this didactic sequence we present different activities to teach English unaccusative verbs in an English class for second language learners. We put forward the idea that grammar must be taught from a generative and inquisitive perspective that promotes the development of creativity, critical thinking and metalinguistic reflexion in order to enhance the acquisition of the target language. Moreover, the type of activities we propose in this sequence enable students to create knowledge.